Bankruptcy Prediction Analysis Using the Grover, Zmijewski, and Springate Models in the Banking Sector Listed on the Indonesia Stock Exchange in 2023 & 2024 - Hermanto, Agus (Business Management, 2025)
This study aims to analyze the accuracy level of bankruptcy prediction models: Grover, Zmijewski, and Springate, within the banking sector listed on the Indonesia Stock Exchange (IDX) during 2023 and 2024.   A quantitative method with a descriptive approach was used. The research sample consisted of 60 banking companies with complete financial reports for 2023 and 2024. Data were analyzed using the three bankruptcy prediction models and compared based on their prediction accuracy. The results indicate that the Grover model has the highest accuracy in predicting financial distress, followed by the Zmijewski model, and lastly the Springate model. These findings are expected to assist companies, investors, and other stakeholders in anticipating bankruptcy risk earlier by selecting the most appropriate prediction model.